2019
DOI: 10.2754/avb201988020219
|View full text |Cite
|
Sign up to set email alerts
|

Long-term oral administration of sweet chestnut (Castanea sativa Mill.) extract does not affect the contraction ability of isolated ileum

Abstract: Extracts of sweet chestnut (Castanea sativa Mill.) which contain hydrolysable tannins are used to prevent diarrhoea in farm animals due to the astringent effect of tannins. The aim of this study was to establish whether long-term treatment with the chestnut extract as a feed additive affects the acetylcholine (ACh)-triggered contractions of isolated rat ileum. Wistar rats of both sexes were divided into 4 male and 4 female groups with 6 animals in each group. The first, second and third groups of both sexes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
2
0
0
Order By: Relevance
“…In this study the increased water intake was also observed in PCOS rats which were also observed in various previous research trials [6]; but the experimental effect of HT was observed to decrease the water intake in rats [42]. However, this effect might be due to the role of HT to maintain the water homeostasis which helped in the prevention of water loss from body [43]. Healthy Reference values: Un-published Data; LDL: High Density Lipoprotein; HDL: Low Density Lipoprotein; TG: Triglycerides; Pc0: Polycystic group with 0% HT; Pc0.5: group with 0.5% HT; Pc1: group with 1% HT; Pc1.5: group with 1.5% HT; Pc2: group with 2% HT Healthy Reference values: Un-published Data; IgG: Immunoglobulin G; IgM: Immunoglobulin M; Pc0: Polycystic group with 0% HT; Pc0.5: group with 0.5% HT; Pc1: group with 1% HT; Pc1.5: group with 1.5% HT; Pc2: group with 2% HT Figures Figure 1 Weekly dry matter intake (%) of PCOS rats…”
Section: Discussionsupporting
confidence: 82%
“…In this study the increased water intake was also observed in PCOS rats which were also observed in various previous research trials [6]; but the experimental effect of HT was observed to decrease the water intake in rats [42]. However, this effect might be due to the role of HT to maintain the water homeostasis which helped in the prevention of water loss from body [43]. Healthy Reference values: Un-published Data; LDL: High Density Lipoprotein; HDL: Low Density Lipoprotein; TG: Triglycerides; Pc0: Polycystic group with 0% HT; Pc0.5: group with 0.5% HT; Pc1: group with 1% HT; Pc1.5: group with 1.5% HT; Pc2: group with 2% HT Healthy Reference values: Un-published Data; IgG: Immunoglobulin G; IgM: Immunoglobulin M; Pc0: Polycystic group with 0% HT; Pc0.5: group with 0.5% HT; Pc1: group with 1% HT; Pc1.5: group with 1.5% HT; Pc2: group with 2% HT Figures Figure 1 Weekly dry matter intake (%) of PCOS rats…”
Section: Discussionsupporting
confidence: 82%
“…In this study the increased water intake was also observed in PCOS rats which were also observed in various previous research trials [8]; but the experimental effect of HT was observed to decrease the water intake in rats [42]. However, this effect might be due to the role of HT to maintain the water homeostasis which helped in the prevention of water loss from body [43].…”
Section: Discussionsupporting
confidence: 82%
“…During this process, tannins precipitate proteins on the surface of intestinal mucosa and thus form stable complexes that act as a protective barrier, preventing infections of intestinal mucosa and water loss through the intestinal wall. Additionally, tannins reduce intestinal motility (Javornik et al 2019).…”
mentioning
confidence: 99%